Epistemic modality in English and Russian. Comparative aspect - Karimberdiyeva , Nadejda Yuldashevna (The Lingua Spectrum, 2026)
Linguists view epistemic modality as a tool for managing speaker commitment, ranging from high certainty to speculative possibility, which is central to both conversational interaction and academic discourse (Hyland, 2015). This study investigates the use of epistemic modality in two distinct fictional works – John Galsworthy’s The Man of Property and J.K. Rowling’s Harry Potter and the Philosopher’s Stone – alongside their Russian translations. The introduction section presents a list of epistemic modal verbs and expressions with their explanatory examples. The methodology involves a comparative analysis of excerpts from the original English texts and their corresponding Russian editions. The results reveal varying degrees of semantic correspondence, categorized into full equivalence, partial equivalence, and the total omission of epistemic modal expressions. Furthermore, the findings highlight a shift in modal usage between 20th-century and contemporary literature. The discussion evaluates these correspondences in terms of “certainty” – the speaker’s commitment to the truth of an utterance – and “pragmatic force,” which dictates the speaker’s perceived tone. Additionally, the study identifies specific linguistic environments that facilitate particular epistemic meanings.